Bullous impetigo with sepsis. - Bhat, Y.R. (European Journal of Pediatric Dermatology, 2016)
Impetigo is the infection of superficial dermis most commonly caused by the organism Staphylococcus aureus. It commonly occurs in young children and bullous impetigo commonly affects neonates. Systemic symptoms are not common and sepsis is rare. Bullous impetigo with extensive lesions, systemic symptoms and sepsis in a newborn was described.